Factors That Influence Women's Interest In Working In The Formal - Non-Formal Sector In Mataram City - Zahra, Mila; Fadliyanti, Luluk; Dzul Fadli, Muhammad (International Journal of Science, Technology & Management, 2025)
This study aims to determine the factors that influence women's interest in working in the formal-non-formal sector in the city of Mataram. This study examines the influence of education, working hours, age, marital status, family status, and health insurance on women's choice of work sector. The formal sector is characterized by legal employment relationships, legal protection, and social security, while the non-formal sector is more flexible but has minimal protection. This study uses an associative quantitative approach. Funds were obtained from the 2023 National Labor Force Survey (Sakernas) with 740 respondents. Data analysis was carried out using logistic regression. The results of the study show that the variables of age, marital status, working hours, education, family status, and health insurance have a significant influence on women's decisions to work, with health insurance being the most dominant factor. These findings emphasize the need for policies that support access to education, social protection, and strengthening the formal sector to increase women's participation and welfare in the world of work.